LOCAL ECONOMIC RESILIENCE STRATEGY DURING THE COVID-19 PANDEMIC: DIGITAL BUSINESS - Hidayati, Firda; Novita, Asti Amelia; Anggoro, Damas Dwi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2022)
The Covid-19 pandemic has caused an economic crisis in Indonesia. Local businesses are the most affected sector. An efficient strategy is needed to overcome the impact of the pandemic so that Micro, Small and Medium Enterprises (MSMEs) can survive in a crisis. Digital business empowerment is one of the solutions. Digital media is used to support marketing activities, financial management, and product promotion through social media, marketplaces, and websites. The purpose of this study is to determine the process of empowering digital businesses to increase MSME business income as a strategy for local economic resilience. This study uses descriptive qualitative research methods with data analysis Strengths, Weaknesses, Opportunities, Threats (SWOT). The results of the study indicate that the community empowerment process is divided into three stages by looking at the enabling, empowering, and protecting aspects. The enabling process shows the potential of handicrafts. Empowering is done through product marketing digitalization training. And protecting as an effort to protect the new system developed in the marketing process